ANALISIS IMPLEMENTASI SISTEM TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN DAERAH (Studi Pada Pemerintah Daerah Kabupaten Kampar) - Elmizar Elmizar; Kasmadi Kasmadi (Jurnal Riset Manajemen Indonesia, 2020)
The application of a non-cash transaction system is a system of development in the transparency of regional financial management. As a follow-up to the implementation of non-cash transactions, the Government of Kampar Regency has implemented a non-cash transaction in full on January 1, 2018 in accordance with the Kampar Regent's Regulation Number: 61 Year 2017 dated December 15, 2017 concerning the Non-Cash Payment System within the Kampar Regency Government. The purpose of this study is to find out the process of implementing a non-cash transaction system in local financial management in Kampar Regency, then to find out the problems and constraints as well as steps for improvement in the process of implementing a non-cash transaction system in regional financial management. The research method used in this research is descriptive qualitative research.The implementation of non-cash transactions by the Kampar District Government has shown a 75% percentage of the level of "Good" implementation. The implementation of the non-cash transaction system at the Kampar Regency government has not been effective because there are still internal and external constraints including limited human resources in financial management, infrastructure limitations to support non-cash transactions, the absence of SOPs in the implementation of non-cash transactions, not all partners have bank accounts and the Treasurer Cash Management System (CMS) application is not yet available.